Direito e cinema - um diálogo possível pela filosofia: contribuição da retórica do cinema para a efetividade do Direito - Almeida, José Rubens Demoro (2017)
This issue aims to verify some characteristics of the legal speech, its rhetoric and language and also aims to build the reality of the legal phenomenon and establish a parallel with the movie language once its also allows an understanding of reality from its sounds, images and movements which cause an impact in the senses. These discussions are presented in order to rework reflexively a world vision, towards a philosophical attitude. The starting point to discuss the mentioned relations consists in presenting law and movies as cultural expressions, which operate in and to the human interaction and which use a specific communication language to describe, direct and dictate behaviour, in order to persuade and seduce the receptor (in law) or the spectator (in movies). So, could the legal speech, mainly directed to the constitution of realities and to order the human behaviour, be known also by the movies and by its language and speech? Could philosophy mediate this contact, establishing a dialogue with the movies to provide a better effectiveness of law? To reach this aim, it is presented a theoretical research related to legal history and speech, its rhetoric and also the development of the movie language. The objective is to demonstrate that it is possible to find huge relations between the legal and movie approaches of the human life